Case study: Nyala company / Amir Imran Mustafha … [et al.] - Mustafha, Amir Imran; Azmi, Nur Nadia; Azllee, Nur Auni Shakirah; Mohd Azmi, Nur Ain Nazurah; Muhammad Ismadi, Yasarah Khairani (2022)
Many young people who dare to start a business at a young age are aware of the risks, but they continue to do so. This is an attempt to know how the theories that have been learned from this subject can be applied in practical situations using business model canvas (BMC). In this case study, we take the opportunity to study at the Nyala company. This company has run the business for almost 3 years by selling candles. However, nyala has its challenges and problems in the business. The major problems are overpriced product, out of stock product, problem website and limited payment method In the research, we could see the findings and results that needed to be highlighted. After selling their product, which is Nyala's candle, they received a lot of negative comments and feedback from customers who were not satisfied with their product. They complained that the candles were too costly and overpriced for them to afford. They can get the same size and quality from other brands at a lower cost. They want to support this business, but most of Nyala's customers are teenagers, and they can only afford it once because it is too expensive. Nyala's candle is also known as an "out of stock" product; their product will sell out in a minute. The customer needs to wait and be alerted about the new update about Nyala's product. This is because Nyala takes a long time to restock their products. Nyala also has an issue with their website; all their product purchases were made through their own website. When they start to sell their candles, the website will crash. Nyala also has a problem with their payment method. Nyala has a limited number of payment options, and its products can be purchased using only three of them. However, several recommendations were provided to solve the problem related to the product. The main point is that Nyala needs to rethink their pricing; they need to sell it at a reasonable price. Nyala also needs to increase their stock as they get a lot of demand. Other than that, Nyala needs to improve the quality of their products in terms of containers and need to expand their sales platform instead of only using a website.